Aspectos históricos dos modelos atômicos nos livros didáticos de química: um mapeamento do período de 1929 a 2018 - Pires, Ronaldo Gonçalves (2021)
The textbook is unquestionably the main source of information used by Chemistry teachers to prepare their classes. Given its importance, it is of utmost importance to consider the effective adequacy of its contents into the historical aspects of science. In order to better understand the insertion of the history of science in Chemistry textbooks, we propose a time-mapping study to answer the following question: What were the main changes promoted by educational legislation and the history of science in the historical approach of atomic models presented in Chemistry textbooks in the period from 1929 to 2018? Our objective was to analyse the insertion of the historical aspects of atomic models in Chemistry textbooks based on a mapping of the contributions of the history of science and legislation. The methodology developed was qualitative, a documentary-like research, using Bardin's content analysis as a technique. One hundred and two (102) textbooks from the collection of the Didactic Book Library of the University of São Paulo and 6 textbooks from the researcher's collection were analysed here. The analysis of the results showed that normative documents on education were decisive in these changes, with emphasis on the agreements between the Ministry of Education and the United States Agency for International Development and the implementation of the National Chemistry Textbook Program. We perceived a clear time lapse in the incorporation of the facts of the history of science to the content within textbooks, which, supported by the theory of Imre Lakatos, we credited as the necessary period for the consolidation of scientific research programs associated with atomic models and the didactic transposition of these facts into school. We conclude that the understanding of the dynamics of content insertion in textbooks can help teachers to use these materials more consciously, inserting the history of science in classes as a factor of humanization of teaching. We also perceive the putative alignment between academic production in the history of science and educational legislators, aiming to improve quality and the scientific relevance of topics in textbooks.